The Reflections Of New Technologies On Film Format And Visual Style: The Psycho Case Within The Context Of Intensified Continuity Editing - Zengin, İbrahim; Oktuğ Zengin, Melis (Medimond S R L, Via Maserati 5, 40128 Bologna, 00000, Italy, 2012)
One of the most distinctive features of cinema from other art forms is that it has a close relationship with technology. Therefore, the history of art forms like painting or sculpture begins with the history of humanity but the invention of cinema begins with the improvements in optical and mechanical sciences which took place in the 19th century. Today, digital technologies dominate all areas of life including the cinema industry and cause fundamental changes in every stage of the cinema industry like shooting or screening processes. The rapid changes experienced in technology provide different perspectives to directors on issues such as camera angles, lighting, editing, sound, and so on. Cinema revealed new forms in parallel with the technological developments but these new forms also led to changes in visual style. These developments in cinema have been a criterion for the history of American cinema. Jaws (directed by Steven Spielberg) which was released in 1975 and the movies like Star Wars (1977, directed by George Lucas) started a new era in the history of American cinema called Contemporary American Cinema. The purpose of this study is to analyse the effect of digital technologies on the movie format and on the visual style with the approach of David Bordwells' intensified continuity editing. As a subject of study the movie Psycho (directed by Alfred Hitchcock) which was shot in 1960 on predigital technologies and the movie Psycho (directed by Gus Van Sant) which was shot in the period of Contemporary American Cinema in 1998 were chosen.
Keywords: Cinema; Digital Technology; Visual Style; Contemporary American Cİnema; Intensified Continuity Editing; Sinema; Dijital Teknoloji; Görsel Stil; Çağdaş Amerikan Sineması; Yoğunlaştırılmış Süreklilik Düzenlemesi